Online advertising: how the consumer goods speaks to women - Munira Hasjim, Muhammad Hasyim, Nursidah, (Opción, 2019)
This research discusses the phenomenon of the product of consumer goods to communicate with women online commercial advertising. The method used is descriptive that try to describe the phenomenon of products interaction to women on online advertisement. The results of this research show that for speaking to women, online commercial advertising sells the social value, like lifestyle and family. In conclusion, one type of communication that exists today besides interpersonal communication, organizational communication, and mass communication is the communication between humans and objects.